Learn to Draw Birds & Butterflies Step-by-step instructions for more than 25 winged creatures - Cuddy, Robbin (CA, USA Quarto publishing group, 2015)
Perfect for young artists-in-training, Learn to Draw Birds & Butterflies offers a comprehensive drawing experience that includes step-by-step lessons, as well as full-color photographs, fun facts, trivia, quizzes, and much more. Each drawing lesson begins with a basic shape, such as a square, a circle, or a triangle, and progresses to a finished colored piece of artwork, making it easy for children to follow along. Along the way, engaging text describes interesting facts about each bird and butterfly. Includes birds such as flamingo, peacock and Kingfisher and butterflies such as Monarch, Red Admiral and Adonis Blue
"64 pages of drwaing fun! contains fun facts, quizzes, color photos, amd mich more!"
Drawing
2
Keywords: Drawing; Juvnile nonficion